Extended Field Postoperative Radiotherapy (EFRT) Yields better Outcomes as Compared to Localised Field RT (LFRT) in Radically Resected Gallbladder Cancer (GBC) - Agrawal, Sushma; Saxena, Rajan (Asian Pacific Journal of Cancer Care, 2020)
Background: Postoperative adjuvant RT is recommended in node positive and positive resection margins patients after radical surgery (RS) in GBC. However there are no guidelines to suggest the regions to be irradiated. Our aim is to compare whether EFRT or LFRT improves outcomes. Methods and Materials: Records of GBC patients who underwent adjuvant chemo-radiotherapy after RS, between January 2007 and December 2014 were reviewed. Demographic data, histopathological data, target delineation, RT treatment planning details, concurrent chemotherapy, side-effects of treatment, and survival data were collated. Patients were treated with either of two techniques: Localised field RT [LFRT] [from 2007-2010] or Extended field RT [EFRT] [from 2011-2014] along with concurrent 5-FU/capecitabine. LFRT involved RT to GB bed, peri-portal, common hepatic artery (CHA) and coeliac lymph nodes and EFRT involved RT to GB bed, peri-portal, CHA, coeliac, gastro-duodenal, superior mesenteric and para aortic lymph nodes. The RT dose was 50.4 Gy/28fractions/5.5 weeks. Loco-regional recurrence rate (LRR), Overall (OS) and Disease free Survival (DFS) was computed with Kaplan Meier method. Results: Out of 60 patients reviewed, 30 were treated with EFRT and 30 with LFRT. There was no significant difference in the acute and late side-effects between the two techniques. At a median follow-up of 44 months (range 36-120 months), 37.5 % patients developed LRR (13.3 % vs 40% in EFRT and LFRT, p = NS).The median OS was not reached (NR) vs 42 months and the median DFS was NR vs 30 months in EFRT vs LFRT respectively (p=0.01 and 0.016). The 5 year OS was 80% vs 42% and 5 year DFS was 80% vs 40% for EFRT and LFRT respectively (p=0.01 and 0.016). Conclusions: Based on our findings, we conclude that EFRT reduces LRR and improves survival in patients with absence of lymphovascular space invasion (LVI) and perineural invasion (PNI). This observation is hypothesis generating and merits validation in a randomised study.